Marketing Management Strategies of Islamic Education Services to Enhance Customer Loyalty: A Case Study of State Islamic Senior High Schools - Ujang Jaenal Mutakin; MA Tihami; Ahmad Qurtubi (Sultan Publisher, 2024)
This study aims to describe the planning, organizing, implementation, and monitoring of Islamic educational service marketing strategies to maintain customer loyalty and to explore their implications. A descriptive qualitative case study approach was used, with purposive sampling selecting principals as critical informants and vice principals, teachers, students, alums, and parents as supporting informants. Data were collected through observation, interviews, and documentation and analyzed using data reduction, presentation, and conclusion drawing. The findings indicate that marketing management strategies at MAN 1 and MAN 2 Cilegon City are implemented but must be fully optimized. Planning involves basic strategies but needs thorough identification, segmentation, positioning, and differentiation. Organizing is relatively effective, with clear task divisions formalized by principal decrees. Implementation follows a marketing mix approach (product, promotion, infrastructure, human resources, and processes), yet promotional efforts still need to be increased. Monitoring is consistently conducted by principals and supporting staff. While customer loyalty is evident, indicated by repeat purchases, recommendations, and cross-product purchases, it is limited to existing market segments and does not reach broader audiences.